Industrial training outcomes: Kulliyyah of Engineering practice as a case study - Ahmad, Salmiah; Abdul Muthalif, Asan Gani; Mel, Maizirwan (2013)

(untitled)
Industrial training that is known as an Engineering Industrial Training (EIT) course is the requirement for all engineering students in order to complete their Bachelor of Engineering degree at the Kulliyyah of Engineering, International Islamic University Malaysia (IIUM). EIT is a very important programme since it complements both the academic and professional aspects of the engineering education though it takes only about 12 weeks period of training. Exposing the students to the practical experience and actual working environment shall open the avenues for developing their skills and capabilities, as well as enhancing their intellectual and emotional persona. The EIT also can provide strong linkages between university-industries that shall pave opportunities for "smart partnerships" and industrially driven research. The outcomes of the EIT that are mainly based on the assessment covering the company’s and university’s evaluation will provide the feedback for students performance after 75% completion of their engineering study. The remarks from the companies on the students will very much helpful for the university to have a continuous quality improvement (CQI) especially on curriculum practiced. This paper provides the EIT course improvement strategy based on the feedbacks from the related parties in executing the EIT at the Kulliyyah of Engineering, IIUM for the cycle of the year 2012.